2019
DOI: 10.1080/14786419.2019.1638385
|View full text |Cite
|
Sign up to set email alerts
|

The chemical constituents of ethanolic extract from Stauntonia hexaphylla leaves and their anti-inflammatory effects

Abstract: Stauntonia hexaphylla (Lardizabalaceae) is an important medicinal plant in Korea, Japan, and China. Its leaves are used to treat many diseases because of their analgesic, sedative, and diuretic effects; however, there are few reports on their chemical constituents and biological activities. This study divided an ethanol extract into dichloromethane (DCM), ethyl acetate (EtOAc), and water fractions. Bioassay-guided fractionation of the ethanol extracts led to the isolation of seven compounds (1−7). Their struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Inflammatory cells produce cytokines, including interleukin (IL)-12 p40, IL-6, and tumor necrosis factor (TNF)-α. IL-12 p40, IL-6, and TNF-α play important roles in the inflammatory response, as well as cell apoptosis and transformation [ 1 ]. Many studies have focused on the inhibition of pro-inflammatory cytokines in an effort to decrease inflammation-related diseases [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory cells produce cytokines, including interleukin (IL)-12 p40, IL-6, and tumor necrosis factor (TNF)-α. IL-12 p40, IL-6, and TNF-α play important roles in the inflammatory response, as well as cell apoptosis and transformation [ 1 ]. Many studies have focused on the inhibition of pro-inflammatory cytokines in an effort to decrease inflammation-related diseases [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing and comparing previous studies and data, the compounds were finally identified as mutongsaponin E and yemuoside YM12 [19][20][21][22]. Similarly, according to fragment ions and our previous experimental data, peaks 8 and 12 were tentatively identified as akebia saponin D and cussonoside A [10,[23][24][25]. Figure 2 clearly shows that the chemical composition and relative content in SHL from different years and seasons are considerably different.…”
Section: Identification and Characterization Of Chemical Constitutionmentioning
confidence: 78%
“…In our previous study, triterpenoid saponins separated from SHL exhibited three types of aglycones, which included oleanolic acid, hederagenin, and akebonic acid [10]. Peak 5 exhibited pseudomolecular ions [M−H] − and [M+NH 4 ] + at m/z 1057.5 and 1076.6 in negative and positive modes, respectively (Additional file 1: Figure S2).…”
Section: Identification and Characterization Of Chemical Constitutionmentioning
confidence: 97%
“…The genus Stauntonia produces various phytochemicals, such as oleanane triterpenoids [6], phenolic glycosides [7] and triterpene saponins [8], which exhibit diverse pharmacological effects including anti-HIV-1 protease [9], anti-gout [10,11], anti-diabetic [12] and anti-osteoporotic [13] effects. In the previous study, we had identified several triterpene glycosides that inhibited the activation of an established macrophage cell line called RAW 264.7 in vitro [14,15]. Previously, oleanane triterpene saponins have shown anti-inflammatory inhibitory effects, such as aster saponin C2 [16], and kalopanaxsaponin B [17].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the preliminary comparison of anti-inflammatory activity of these saponins with their aglycon was also discussed. Additionally, to investigate the in vivo efficacies of the saponins and the aglycon, we performed an animal experiment widely used for determining macrophage-dependent immune response, i.e., the lipopolysaccharide (LPS)-induced mouse sepsis model, administered orally with either the saponin or the aglycon beforehand [14,15,18]. Several studies have reported using liquid chromatography with tandem mass spectrometry (LC-MS/MS) to measure the content of saponins in herbal medicines for better accuracy [20].…”
Section: Introductionmentioning
confidence: 99%